2001
DOI: 10.1002/1097-0142(20010915)92:6+<1725::aid-cncr1504>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue during preoperative chemoradiation for resectable rectal cancer

Abstract: BACKGROUND The aim of this study was to evaluate the severity and patterns of fatigue during preoperative chemoradiation therapy for locally advanced rectal cancer and determine whether there are predictors for patients who develop severe fatigue. METHODS Seventy‐two patients with resectable rectal cancer received chemoradiation (total radiation dose, 45 gray/25 fractions to the pelvis; continuous infusion of 5‐fluorouracil [300 mg/m2]). The Brief Fatigue Inventory (BFI), a measure that categorizes fatigue sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…Another recent study evaluated pain and fatigue in elderly cancer patients and their association with other symptoms [28]. Patients were aged over 65 years, had newly diagnosed cancer of the breast, colon, lung, or prostate, and were followed for 1 year.…”
Section: Treatment-related Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Another recent study evaluated pain and fatigue in elderly cancer patients and their association with other symptoms [28]. Patients were aged over 65 years, had newly diagnosed cancer of the breast, colon, lung, or prostate, and were followed for 1 year.…”
Section: Treatment-related Fatiguementioning
confidence: 99%
“…In some studies fatigue has been significantly higher in patients than in a control population, and in other studies no difference was evident [26][27][28][29][30][31]. Many studies test variably constructed groups using different assessment tools, and others have not included control subjects.…”
Section: Fatigue In Cancer Survivorsmentioning
confidence: 99%
“…In patients with adjuvant irradiation for conservatively operated breast cancer, it might be the only treatment toxicity. Some studies focus on the time course of radiation-induced fatigue during therapy, showing that fatigue intensity peaks during the last weeks of treatment and that it subsides in the weeks following therapy (Ahsberg and Furst 2001;Geinitz et al 2001; Greenberg et al 1992; Greenberg et al 1993; Monga et al 1999;Smets et al 1998a; Wang et al 2001). Little is known about fatigue during long-term follow-up after radiation therapy and its relation to pretreatment fatigue levels (Smets et al 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…34,35 While there is a consistent association between fatigue and anemia in cancer patients, 6,36-39 anemia is not the only factor responsible for fatigue as there is fatigue in nonanemic patients and there are anemic patients without fatigue. 40 We found that anemia is an independent factor for IADL dependencies. This is a new finding in cancer patients though it has been abundantly demonstrated in geriatric patients.…”
Section: Discussionmentioning
confidence: 69%